An examination of injection drug use trends in Victoria and Vancouver, BC after the closure of Victoria's only fixed-site needle and syringe programme - Ivsins, A.; Chow, C.; Macdonald, S.; Stockwell, Tim; Vallance, K.; Marsh, D.; Michelow, W.; Duff, C. (2012)
Background: Needle and syringe programmes (NSPs) have been established as effective harm reduction initiatives to reduce injection drug use (IDU)-related risk behaviours, including sharing needles. On May 31, 2008, Victoria, BC's only fixed site NSP was shut down due to community and political pressure. This study examines and compares IDU trends in Victoria with those in Vancouver, BC, a city which has not experienced any similar disruption of IDU-related public health measures. Methods: Quantitative and qualitative data were collected by interviewer-administered questionnaires conducted with injection drug users (n= 579) in Victoria and Vancouver between late 2007 and late 2010. Results: Needle sharing increased in Victoria from under 10% in early 2008 to 20% in late 2010, whilst rates remained relatively low in Vancouver. Participants in Victoria were significantly more likely to share needles than participants in Vancouver. Qualitative data collected in Victoria highlight the difficulty participants have experienced obtaining clean needles since the NSP closed. Recent injection of crack cocaine was independently associated with needle sharing. Conclusions: The closure of Victoria's fixed site NSP has likely resulted in increased engagement in high-risk behaviours, specifically needle sharing. Our findings highlight the contribution of NSPs as an essential public health measure.